Involvement of microRNAs-449/FASN axis in response to trastuzumab therapy in HER2-positive breast cancer - Ana Lameirinhas; Sandra Torres-Ruiz; Iris Garrido-Cano; Cristina Hernando; María Teresa Martínez; Ana Rovira; Joan Albanell; Sandra Zazo; Federico Rojo; Begoña Bermejo; Ana Lluch; Juan Miguel Cejalvo; et al. (Molecular Medicine)
Abstract The anti-HER2 monoclonal antibody trastuzumab and new derivative formulations are the standard treatment for HER2-positive breast cancer. However, after 1 to 5 years of treatment, some patients acquire resistance to therapy, leading to relapse. The microRNA-449 family members were downregulated in HER2-positive breast cancer cell lines and low levels were associated with patients’ worse prognosis. Moreover, trastuzumab-resistant HER2-positive breast cancer cell lines showed lower microRNAs-449 and higher Fatty Acid Synthase (FASN) expression, compared to sensitive cell lines. The direct regulation of FASN by microRNA-449a and microRNA-449b-5p was demonstrated. Moreover, microRNAs-449 overexpression and FASN inhibition decreased cell proliferation and sensitized cells to trastuzumab treatment by inhibiting the PI3K/AKT signaling pathway. Together, these results suggest the microRNAs-449/FASN axis as a potential therapeutic target in combination with anti-HER2 agents to overcome trastuzumab resistance and to improve treatment response in HER2-positive breast cancer patients.